Antidiabetic potential of Chia (Salvia hispanica L.) Seed Oil in streptozotocin induced diabetic rat - Dalginli, KY; Kilicle, PA; Atakisi, O; Ozturkler, M; Uluman, E (Journal of the Hellenic Veterinary Medical Society, 2023)
Chia seed oil (CSO) is a natural carotenoid that has active pharmacological properties and has been the most popular in recent years. The aim this study was to investigate the hypoglycemic antioxidative/nitrosative, oxidative DNA damage and adenosine deaminase effects of chia seed oil on streptozotocin induced diabetes in rats. Sprague Dawley, adult, male rats were used in the study. Animals were divided into the following groups: Group I (Control, n=7), Group II (Chia Group, Chia seed oil (CSO) was applied by oral gavage at 1g/kg for 14 days, n=7), Group III ((Diabetes (DM) Group, Streptozotocin (STZ) was applied as 50 mg/kg i.p. single dose (n=7)), and Group IV (DM+CSO Group, STZ 50 mg/kg i.p. single dose +CSO was applied by oral gavage at 1g/kg for 14 days after diabetes was induced, (n=7)). Physiological parameters (body weight, blood glucose) were evaluated. STZ exposure increased serum TOS, OSI and NO levels, which are markers associated with oxidative damage, while PON enzyme activities decreased compared to the control group and did not change TAS levels. Moreover, 8-OHdG level and ADA activity were increased in the diabetic groups. In addition, it was found to regulate body weight and increased glucose in the diabetic group. Our results show that Chia treatment effectively counteracts oxidative stress-mediated free radicals damage caused by diabetes and may serve as a therapeutic agent in reducing oxidative damage in diabetic subjects.